Synthesis and Antiviral Activity of Water‐Soluble Polycarboxylic Derivatives of [60]Fullerene Loaded with 3, 4‐Dichlorophenyl Units. Issue 11 (29th October 2018) - Voronov, Ilya I.; Martynenko, Vyacheslav M.; Chernyak, Alexander V.; Balzarini, Jan; Schols, Dominique; Troshin, Pavel A.
Abstract: We have synthesized a series of water‐soluble polycarboxylic derivatives of [60]fullerene with a gradually changed polarity by combining three to five polar (ionic) malonate addends with two to zero hydrophobic dichlorobenzene units and explored their antiviral activity. It has been shown that decreasing the number of the ionogenic carboxylic groups in the molecules enhanced their antiviral activity against HIV‐1 and suppressed their action against HIV‐2. The obtained results implied that the charged states and hydrophobicity of the water‐soluble polycarboxylic fullerene derivatives affect significantly their biological properties. Abstract :